Aspek Hukum Dalam Proses Kliring Untuk Pengaturan Uang Giral Di Indonesia - Amini, Fitri (Journal Of Law And Social Society, 2024)
The clearing system plays a strategic role in ensuring the smooth flow of giro payment transactions as a vital part of the national payment system. Clearing serves to settle interbank obligations efficiently and securely, aiming to establish stability and certainty in financial transactions. This study examines the legal aspects underlying the implementation of clearing in Indonesia, including regulations enforced by Bank Indonesia as the supervisory authority. Additionally, it identifies legal challenges, such as potential disputes between banks, customer protection issues, and compliance with prevailing regulations. By employing a juridical approach, this study aims to provide recommendations to enhance the effectiveness and legal certainty of the clearing system, thereby supporting the development of a more transparent, accountable, and efficient payment system in Indonesia.